The Role of Language Use in Reports of Musculoskeletal Pain Among Hispanic and Non-Hispanic White Adolescents. (March 2017) - Zamora-Kapoor, Anna; Omidpanah, Adam; Monico, Evelyn; Buchwald, Dedra; Harris, Raymond; Jimenez, Nathalia
Objective: This study examined the role of English language use in the reported frequency of musculoskeletal pain among Hispanic and non-Hispanic White youth.Method: This is a secondary data analysis using a cross-sectional sample of 12, 189 Hispanic and non-Hispanic White adolescents recruited for the National Longitudinal Study of Adolescent to Adult Health. Respondents were classified into three groups: (a) English-speaking non-Hispanic Whites, (b) English-speaking Hispanics, and (c) Spanish-speaking Hispanics.Results: After controlling for body mass index and demographic, socioeconomic, and behavioral variables, Spanish-speaking Hispanics reported the least frequent musculoskeletal pain ( OR = 0.415, 95% CI [0.361, 0.477]; p < .001), followed by English-speaking Hispanics ( OR = 0.773, 95% CI [0.690, 0.865]; p < .001).Conclusion: The experience of musculoskeletal pain is a physiological as well as a cultural phenomenon.Implications for Practice: Health care providers should consider the role of language use in reports of pain in Hispanic and non-Hispanic White adolescents.